2015
DOI: 10.3390/rs70404002
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Point or Polygon Based Training Data on RandomForest Classification Accuracy of Wetlands

Abstract: Wetlands are dynamic in space and time, providing varying ecosystem services. Field reference data for both training and assessment of wetland inventories in the State of Minnesota are typically collected as GPS points over wide geographical areas and at infrequent intervals. This status-quo makes it difficult to keep updated maps of wetlands with adequate accuracy, efficiency, and consistency to monitor change. Furthermore, point reference data may not be representative of the prevailing land cover type for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…In addition, perennial canopy cover from coniferous forests can obscure small wetlands and transitional zones from optical sensors, particularly moderate resolution Landsat data (Corcoran et al. ; Gallant ). These issues are further compounded by the relative scarcity of wetlands and riparian areas on the landscape, which makes it difficult to distinguish small wetlands nested within larger land cover classes (Wright and Gallant ; Millard and Richardson ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, perennial canopy cover from coniferous forests can obscure small wetlands and transitional zones from optical sensors, particularly moderate resolution Landsat data (Corcoran et al. ; Gallant ). These issues are further compounded by the relative scarcity of wetlands and riparian areas on the landscape, which makes it difficult to distinguish small wetlands nested within larger land cover classes (Wright and Gallant ; Millard and Richardson ).…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly important in forested regions, as remotely sensed elevation data can describe the vertical structure of terrain obscured by canopy (Corcoran et al. ). LiDAR DEMs have been shown to be especially effective for capturing these features (Millard and Richardson ; Huang et al.…”
Section: Introductionmentioning
confidence: 99%
“…A LiDAR dataset is available for the entire bog and surrounding area. A number of recent studies have demonstrated that LiDAR derivatives provide superior classification accuracies compared with use of optical and radar imagery (e.g., [25][26][27][28][29]) for both general land cover mapping and specifically in peatland mapping. Optical imagery captures spectral reflectance from the different vegetation species visible from above.…”
Section: Study Area and Datamentioning
confidence: 99%
“…Corcoran and colleagues [86] evaluated the benefits of using points, point-centered windows, and image objects to train the Random Forests decision-tree classifier, then considered the benefits contributed by different variables derived from color-infrared orthoimagery and lidar data to generate classifications for two wetland landscapes in Minnesota, USA. Millard and Richardson [87] used lidar-derived variables to evaluate a suite of effects of different characteristics of training data selection on the Random Forests classifier.…”
Section: Purpose Of This Special Issuementioning
confidence: 99%